Analysis of Transcriptomic Changes in Bovine Endometrial Stromal Cells Treated With Lipopolysaccharide - Ding, Xuefen; Lv, Haimiao; Deng, Lixin; Hu, Wenju; Peng, Zhan; Yan, Chenbo; Yang, Dexin; Tong, Chao; Wang, Xinzhuang (Frontiers in Veterinary Science, 2020)
Endometritis adversely affects the ability of cattle to reproduce, and significantly reduces milk production. The endometrium is mainly composed of epithelial and stromal cells and they produce the first immune response to invading pathogens. However, most of the epithelial cells are disrupted and stromal cells are exposed to an inflammatory environment when endometritis occurs, especially postpartum. A loss of the protective epithelium allows bacteria or toxins to access stromal cells. The activation of Toll-like receptor（TLRs）on stromal cells induces increased production of cytokines. Understanding the genome-wide characterization of the bovine endometritis will be beneficial for prevention and treatment of endometritis. In this study, whole-transcriptomic gene changes in bovine stromal cells treated with LPS were compared with those treated with PBS (control group) and were analyzed by RNA sequencing. Compared with the control group, a total of 366 differentially expressed genes (DEGs) were identified in LPS-induced group (234 upregulated and 132 downregulated genes), with an adjusted P-value＜0.05 by DESeq. Gene ontology (GO) enrichment analysis revealed DEGs were most enriched in interleukin-1 receptor binding, regulation of cell activation, and lymphocyte-activated interleukin-12 production. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed DEGs were most enriched in TNF signaling pathway, Toll-like receptor signaling pathway, cytokine-cytokine receptor interaction, NF-κB signaling pathway, and chemokine signaling pathway. The results of this study unraveled bovine endometrial stromal cells affected with LPS transcriptome profile alterations, which may have a significant effect on the treatment inflammation by comprehending molecular mechanisms and authenticating unique genes related to endometritis.